Cultural Bridges Enhancing Performance of Expatriates in Indonesia and Locals Abroad Through Innovative Human Resource Practices - Dartanto, Early Salsabiila Noveli Lovita; Prabowo, Roneisha Raissa; Limantara, Louisa Arthur; Aisyah, Rheyna Jufri Sifa Zie; Samosir, Adriel Rodclifford (LPPM of NAROTAMA UNIVERSITY, 2025)
Cultural diversity presents both opportunities and challenges for expatriates working in Indonesia and local employees adapting abroad. This study examines the role of innovative Human Resource (HR) practices in enhancing cross-cultural performance. Findings highlight key challenges, including differences in social norms, language barriers, and cultural misunderstandings, which can lead to stress, decreased performance, and assignment failures. HR strategies such as cross-cultural training, onboarding, and mentoring have proven effective in reducing these challenges, fostering job satisfaction, and improving team collaboration. Adaptive leadership that embraces local cultural contexts significantly enhances trust and productivity. Furthermore, expatriates act as knowledge bridges, transferring technical and cultural insights to local teams, strengthening organizational cohesion. Case studies, including PT Freeport Indonesia and PT Haier Sales Indonesia, underscore the importance of tailored HR practices and leadership in mitigating cultural differences and driving organizational success. Beyond formal training, practical strategies like mentorship, community engagement, and language acquisition are essential for effective adaptation. This research emphasizes that holistic approaches to cross-cultural integration not only enhance individual performance but also create a more inclusive and collaborative workplace.